Intentions to Be an Athletic Director: Racial and Gender Perspectives. (April 2017) - Wells, Janelle E.; Kerwin, Shannon
The aim of this study was to evaluate senior athletic administrators' expectations and intentions of becoming National Collegiate Athletic Association (NCAA) Division I athletic directors (ADs) and explore women and racial minority senior athletic administrators' athletic workplace experience. To serve the purpose, two studies using social cognitive career theory (SCCT) were employed. First, demographic (i.e., gender and race) differences by SCCT variables were assessed through survey collection and multivariate analysis of variance. Second, content analysis of interviews was used to assess the experiences of athletic administrators. Results revealed women and racial minority senior athletic administrators' had similar self-efficacy compared to White men, but they encountered more barriers, unfavorable outcome expectations, and lower choice goals associated with becoming an NCAA Division I AD. Further, findings show women and racial minority senior athletic administrators felt occupational segregation limited their access and opportunities for career advancement to a Division I AD position.